Influence of Fertilizer and Weed Management Practices on Yield, Economics and Post-harvest Soil Properties of Onion (Allium cepa L.) - Mishra, N.; Sahoo, K. C.; Ray, M.; Prusty, M.; Panda, N.; Mohanty, K. K.; Dhal, P. (International Journal of Bio-resource and Stress Management, 2024)
A field experiment was carried out during rabi season (September–March) of 2017–18 and 2018–19 at the experimental plot of RRTTS, OUAT, Keonjhar, Odisha to evaluate the nutrient and weed management practices on performance of onion. Fifteen treatmentswere designed in a split plot design. Among all the treatments, the maximum plant height was recorded in N3W4 (56.29 cm) which was closely followed by N3W3 (55.97 cm), number of leaves plant-1 was higher in N3W3 (12.47) significantly which was closely followed by N2W4 (12.33) and N2W3 (12.00) and maximum neck thickness was recorded in N1W2 (1.39 cm). Among yield parameters, the average bulb weight of onion ranges from 33.56 g (N1W2) to 87.6 g (N2W3) while, the highest bulb yields of onion (17.37 and 20.40 t ha-1) was recorded for the treatment which to be exact was applied with pre-emergence application of pendimethalin @ 0.8 l ha-1 supplement with one hand weeding at 25 DAT with B:C ratio of 1.84 and 1.76 for the year 2017–18 and 2018–19 respectively. Similarly, the treatment combination of N2W3 i.e. application of 50% STBFR along with 50% FYM based on N requirement and pre-emergence application of pendimethalin @ 0.8 l ha-1+onehand weeding at 25 DAT) was recorded the highest. The available nutrients like nitrogen, phosphorus, potash and sulphur content (284.67 kg ha-1, 14.83 kg ha-1, 97.43 kg ha-1 and 11.40 kg ha-1) in the post-harvest soil was recorded highest with the treatment N2W3.